Chronic Oral D-Galactose Induces Oxidative Stress but Not Overt Organ Dysfunction in Male Wistar Rats - Jelena Martinovic; Ivana Gusevac Stojanovic; Sladjan Nesic; Ana Todorovic; Katarina Bobic; Sanja Stankovic; Dunja Drakulic (Current Issues in Molecular Biology)
D-galactose (d-gal) plays numerous roles in the organism as an energy-providing nutrient and also an important constituent of the complex glycoconjugates. However, excessive amounts of d-gal activate alternative metabolic pathways that can lead to the development of a pro-oxidative environment. This feature is used in numerous aging studies which implied intraperitoneal (i.p.) or subcutaneous (s.c.) administration of d-gal for a prolonged time. The present study aims to investigate the systemic effects of orally administered d-gal (200 mg/kg and 500 mg/kg, dissolved in tap water, for 6 weeks) by analyzing oxidative stress parameters in the liver, kidney, and heart. For comparison with natural aging, the effects were studied in rats aged 12, 18, 24, and 30 months. In addition, histopathologic analyzes and serum biochemical measurements were performed to investigate the potential structural and functional organ damage induced by d-gal administration. Our findings show that chronic oral administration of d-gal induces oxidative stress in rat organs and mimics some aspects of natural aging similar to those of 30-month-old rats. Consistent with its primary role in galactose metabolism, the liver exhibited the most pronounced oxidative damage. However, despite the increased oxidative stress, only minor histopathological changes were observed, while organ function remained largely unaffected. Oral intake of d-gal was found to have milder effects compared to i.p. or s.c. injections, suggesting that this model may induce some features of natural aging but without overt organ dysfunction.